2004
DOI: 10.1111/j.1601-5223.1995.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Interspecific Crossing Experiments in Facultatively Apomictic Blackberries (Rubus subgen. Rubus) Using DNA Fingerprinting

Abstract: A series of interspecific crossing experiments in Rubus was evaluated with DNA fingerprinting to assess the proportion of apomictic vs sexual seed set. A total of 71 seedlings and their putative parents were thus analyzed by hybridization of HaeIII‐digested DNA samples to a minisatellite DNA probe derived from the M13 phage. Of the offspring derived from non‐hybridogenous seed parents, only about 10% appear to emanate from sexual seed set. On the contrary, offspring derived from pollination of hybridogenous pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 23 publications
1
17
1
Order By: Relevance
“…The pseudogamous apospory occurring in R. alceifolius in its area of introduction is the same type of apomixis as that described in European species of the subgenus Rubus (Thomas, 1940;Gustafsson, 1943;Nybom, 1988Nybom, , 1995Weber, 1995;Kollmann et al, 2000). To determine whether fruit-set from non-pollinated flowers results from apomixis or autogamy, individuals with heterozygous microsatellite loci are necessary (Amsellem et al, 2001 ).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The pseudogamous apospory occurring in R. alceifolius in its area of introduction is the same type of apomixis as that described in European species of the subgenus Rubus (Thomas, 1940;Gustafsson, 1943;Nybom, 1988Nybom, , 1995Weber, 1995;Kollmann et al, 2000). To determine whether fruit-set from non-pollinated flowers results from apomixis or autogamy, individuals with heterozygous microsatellite loci are necessary (Amsellem et al, 2001 ).…”
Section: Discussionmentioning
confidence: 84%
“…Among the 12 subgenera of the genus Rubus, apomixis prevails in the subgenus Rubus, only in polyploid taxa, under the form ofpseudogamous apospory. In this type of apomixis, asexual reproduction takes place, but the endosperm may require fertilisation to develop (Crane, 1940;Thomas, 1940;Gustafsson, 1943;Jennings et al, 1967;Czapik, 1981Czapik, , 1983Nybom, 1985Nybom, , 1988Nybom, , 1995Richards, 1986;Weber, 1996;Kollmann et al, 2000;van Dijk & van Damme, 2000). Apomixis also occurs in polyploid species from other subgenera of Rubus (Petrov, 1939;Pratt & Clausen, 1958;Nybom, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybridisation between apomictic lineages of Rubus subgen. Rubus is possible as a result of re-sexualisation followed by pollination, as was proved in DNA research (Nybom 1995;Werlemark & Nybom 2003). Lidforss (1905Lidforss ( , 1907 showed that primary hybrids between apomictic species seem to be largely sexual.…”
Section: Recent Modifications and Critiquesmentioning
confidence: 94%
“…Apomictic reproduction combines both diplospory and apospory, and this mode of reproduction can be influenced by environmental factors (Šarhanová et al 2012). Especially in tetraploids, retained sexuality can be considerable (Antonius & Nybom 1995;Nybom 1995), but triploid and pentaploid taxa are almost obligate apomicts (Šarhanová et al 2012). Artificial hybrids are rather easily obtained, not only when a sexual partner is involved, but also between apomict lineages.…”
Section: Diversity Taxonomy and Systematicsmentioning
confidence: 99%